Application of Effective Clapping and Coughing Techniques Post Nebulization to Overcome Airways Clearance in Asthma Patients - Hendrawati Hendrawati; Wulandari Wulandari; Fuzianti Lestari (Indonesian Journal of Global Health Research, 2024)
Asthma is one of the main diseases that cause patients to require hospitalization. WHO records 235 million cases of asthma worldwide each year. In Indonesia, the number of asthma sufferers is 4.5% of the total population or 12 million. At Grha Permata Ibu Hospital, there are 113 asthma sufferers out of a total of 9,654 patients. Asthma causes the airways to narrow because they are blocked by mucus/phlegm. Therefore, appropriate treatment such as pharmacological management with nebulization therapy & non-pharmacological chest physiotherapy and effective coughing techniques are needed to clear the respiratory tract of obstructing phlegm. Objectives to determine the application of effective post-nebulization clapping & coughing techniques to overcome airway clearance in asthma sufferers. The type of research is quantitative descriptive. The methods used by the author are interviews, physical examinations, & observations. The instruments used are informed consent sheets, assessments, observations & questionnaires. Before the intervention, all respondents experienced problems with airway clearance with clinical shortness of breath, coughing and difficulty expelling phlegm. After the intervention, the results showed that the clapping technique & effective coughing post nebulization were able to reduce shortness of breath, as many as 66.6% of respondents said that shortness of breath was reduced, 33.3% of respondents said they were not short of breath and 73.3% of respondents were able to expel phlegm. Implementation of clapping and coughing techniques effectively after nebulization to overcome airway clearance in asthma sufferers.